Oral cleanness and periodontal health status among coffee-shop workers in Najaf city / Iraq - Amjed M Sahib; Nada J Radhi (College of Dentistry/ University of Baghdad, 2018)
Background: Water-pipe can be defined as a single or multi stemmed device that used to vaporize and smoke flavored tobacco whose smoke is passed via water vase before inhalation. Water-pipe smokers are at risk of exposure to many toxic chemicals that are not filtered by water, as well as risk of infectious diseases when the mouth piece of the water-pipe is shared. This study was carried out to investigate the effect of water pipe on the oral health. Materials and Methods: Sixty persons were included in this study aged between 22 and 23 years. Forty persons were coffee shop workers for at least five years, half of them were water-pipe smokers (active smokers) and the other weren't smokers (passive smoker), the last group was the control group which includes twenty non-smoker students matching the study group in the age, gender and geographical location. They had been diagnosed for plaque index of Silness and Leo in1964, calculus index according to calculus component of the Periodontal Disease Index, (PDI) of Ramfjord 1959 and gingival index of Löe and Sillness 1963 as well as loss of attachment according to criteria of WHO in1997. The values of the present study were subjected to statistical analysis by Statistical Package for Social Sciences version 20 to specify the statistical differences between the three groups. The Kruskal-wallis test was used to determine the statistical significance of difference between the three groups. Mann-Whitney test was used to assess the statistical significance of difference between each 2 groups. Results: The mean rank values of dental plaque were recorded to be the highest among the coffee shop workers who were active water-pipe smokers group followed by the workers who were passive water-pipe smokers then control with statistically highly significant difference. Similar results were obtained concerning gingival and calculus indices with statistically highly significant difference. There is no significant difference concerning the attachment loss attachment loss among water-pipe smokers and the control group. Conclusions: this study concluded that water-pipe smoking is negatively associated with the oral cleanness and gingival health.